IMPLEMENTASI PENDIDIKAN KARAKTER DI MAN 1 KOTA KENDARI - Amiruddin Amiruddin (Balai Penelitian dan Pengembangan Agama Makassar, 2018)
This study aims to seen the implementation of character education ineducational units especially in Madrasah Aliyah, which focus on theimplementation of character education and supporting and inhibiting factors inthe implementation of character education MAN 1 Kendari. This study used aqualitative approach through simple observation of the curriculum charactermanagement, a brief interview with the headmaster and educators, conductvisual documentation of the facilities and infrastructure, and literature on somerelated literature. The results of this study, 1) In implementative of charactereducation in MAN 1 Kendari has long been applied through the guidance ofreligion, its application is not in the form of subjects (monolithic), but integratedinto the process of learning, self development activities/extracurricular, andfamiliarization school, 2) Factors supporting the implementation of charactereducation to the support of the Ministry of Religious Affairs in the form ofsocialization of character education in each of the activities, the involvement ofsupervisors in providing guidance, the role of school committee in support of allthe program launched by the madrasah, caring headmaster, teachers andeducation personnel in create a religious atmosphere in the madrasah in thehope of fostering the realization of a noble character to the students, as well asthe role of the organization madrasah. Inhibiting factors in implementing acharacterized curriculum in the absence of regulation that can be used as alegal umbrella for the implementation of character education in madrassas,some educators do not understand the concept of planting character values thatwill be developed in each learning process and the role of supervisors who arenot yet maximal.